Dickeya fangzhongdai was prevalent and caused taro soft rot when coexisting with the Pectobacterium complex, with a preference for Araceae plants - Zhang, Jingxin; Sun, Dayuan; Shen, Huifang; Pu, Xiaoming; Liu, Pingping; Lin, Birun; Yang, Qiyun (Frontiers in Microbiology, 2024)
Bacterial soft rot caused by coinfection with Dickeya spp. and Pectobacterium spp. in hosts can cause successive changes in fields, and it is difficult to prevent the spread of and control the infection. Pectobacterium spp. are prevalent in the growing areas of tuberous crops, including taro and potato. Recently, Dickeya fangzhongdai has emerged as a virulent pathogen in taro. To determine the prevalence status of the causal agents and evaluate the potential spreading risks of D. fangzhongdai, screening and taxonomic classification were performed on phytopathogenic bacteria collected from different taro-growing areas in Guangdong Province, China, and biological and genomic characteristics were further compared among typical strains from all defined species. The causative agents were verified to be phytobacterial strains of D. fangzhongdai, Pectobacterium aroidearum and Pectobacterium colocasium. P. aroidearum and P. colocasium were found to form a complex preferring Araceae plants and show intensive genomic differentiation, indicating their ancestor had adapted to taro a long time prior. Compared with Pectobacterium spp., D. fangzhongdai was more virulent to taro corms under conditions of exogenous infection and more adaptable at elevated temperatures. D. fangzhongdai strains isolated from taro possessed genomic components of additional T4SSs, which were accompanied by additional copies of the hcp-vgrG genes of the T6SS, and these contributed to the expansion of their genomes. More gene clusters encoding secondary metabolites were found within the D. fangzhongdai strains than within the Pectobacterium complex; interestingly, distinct gene clusters encoding zeamine and arylpolyene were both most similar to those in D. solani that caused potato soft rot. These comparisons provided genomic evidences for that the newly emerging pathogen was potentially equipped to compete with other pathogens. Diagnostic qPCR verified that D. fangzhongdai was prevalent in most of the taro-growing areas and coexisted with the Pectobacterium complex, while the plants enriching D. fangzhongdai were frequently symptomatic at developing corms and adjacent pseudostems and caused severe symptoms. Thus, the emerging need for intensive monitoring on D. fangzhongdai to prevent it from spreading to other taro-growing areas and to other tuberous crops like potato; the adjustment of control strategies based on different pathopoiesis characteristics is recommended.